مدينة الوادي لحساب شدة الإشعاع الشمسي FORTRAN استعمال - لبیھیات, فطیمة; عطیة, مباركة (university of eloued جامعة الوادي, 2014)
الشمس عبارة عن كرة غازیة حیث تؤدي الإنصھارات الحاصلة في مركز الشمس إلى إصدار إشعاع كھرومغناطیسي عالي التردد یسمى بالإشعاع الشمسي و یصل ھذا الإشعاع إلى سطح الأرض ولكنھ في طریقھ یتعرض إلى عوائق لذا ینقسم إلى ثلاثة أنواع: مباشر ،منتشر،كلي ولتثبیت اللواقط الشمسیة یجب معرفة كمیة الإشعاع الشمسي الساقط في منطقة معینة ولھذا یجب معرفة المعطیات الجغرافیة ( الإرتفاع عن سطح البحر ،البعد عن خط غرینیتش ° 6.8833 ،وخط الإستواء ° 33.33 ) وھذه الأخیرة إستعملناھا في حساب شدة حیث بینت النتائج المتحصل علیھا لمنطقة ، FORTRAN الإشعاع الشمسي بواسطة برنامج الوادي أنھا تستقبل كمیات كبیرة من الإشعاع الشمسي و ھذا لكون المنطقة المدروسة صحراویة.The sun is a boll of gas where lead fusions taking place in the centre of the sun to the issuance of hight frequency electromagnetic radiation called solar radiation and to reach the Earth surface ,but in a way expaced to obstructions so devided into three type: commantay ,total,iswidespread to installe solar collectors must know the amount of solar radiation incident on a given area and therfore must know the geographical data(altitude auay from the line of greenuwiche 6.8833 degree ,for from the equator 33.33 degree ) and we rised the latter in the intensity of solar radiation by a program where FORTRAN showed the results obtained for Eloued it receives large amounts of solar radiation this is what appears tobe adesert ared studied
مذكرة ليسانس فيزياء